2021
DOI: 10.2478/sjph-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-up an integrated care for patients with non-communicable diseases: An analysis of healthcare barriers and facilitators in Slovenia and Belgium

Abstract: Introduction Although the concept of integrated care for non-communicable diseases was introduced at the primary level to move from disease-centered to patient-centered care, it has only been partially implemented in European countries. The aim of this study was to identify and compare identified facilitators and barriers to scale-up this concept between Slovenia and Belgium. Methods This was a qualitative study. Fifteen focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Because most participants in our study reported a lack of information, there is a need for better information flow between levels of care and with certain other professionals or institutions (dietitians, collaboration between family medicine practice and nursing home), for example, by sharing data and allowing online meetings [ 22 ]. This would facilitate integration and improve integrated patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because most participants in our study reported a lack of information, there is a need for better information flow between levels of care and with certain other professionals or institutions (dietitians, collaboration between family medicine practice and nursing home), for example, by sharing data and allowing online meetings [ 22 ]. This would facilitate integration and improve integrated patient care.…”
Section: Discussionmentioning
confidence: 99%
“…SCUBY is an international research project funded by the EU under the Horizon2020 Framework Programme with contract number 825432 - SCUBY. Some of the results from the SCUBY project have already been published [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies reporting on similar initiatives show better health outcomes and reduction in preventable hospitalizations and emergency departments use [ 58 ]. Yet, the implementation and the sustainability of such initiatives have proved challenging over the years [ 17 59 60 ]. Key informants from both programs reflected on these challenges in the Quebec context, offering a better understanding of the elements that facilitate and hinder such initiatives and enabling comparisons across countries.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there is still a lack of optimal care for chronically ill patients, especially for members of vulnerable groups ( 6 ). Research in Slovenia discovered that one possible cause of this is the low level of patient empowerment and suboptimal implementation of teamwork and coordinated care, which must approach the patient and move from healthcare institutions to each patient’s local and home environment ( 12 , 13 ). Primary healthcare in Slovenia needs improved measures to support self-management of chronically ill patients ( 13 ).…”
Section: Introductionmentioning
confidence: 99%